Fernando Martínez-Gil & Alfonso Morales-Front (eds.), Issues in the phonology and morphology of the major Iberian languages. Georgetown University Press, Washington, DC, 1997; 694 pp. - Herrera Zendejas, Esther (Nueva Revista de Filología Hispánica (NRFH), 1998)
Se reseñó el libro: Issues in the phonology and morphology of the major Iberian languages.